Traditions of theology : studies in Hellenistic theology, its background and aftermath - Frede, Dorothea, 1941-.; Laks, André. (Philosophia Antiqua, 2002)
The nine articles in this volume were orginally presented at the VIII. Symposium Hellenisticum in Lille in August 1998. The authors discuss a set of theological questions that were central to the doctrines of the dominant schools in the Hellenistic age, such as the existence of the gods, their nature, and their concern for humankind. While the philosophers of the Classical age had kept their distance from conventional religion, the Stoics and Epicureans saw the need to come to terms with the religious tradition both in a critical and in a supportive sense. Especially the challenge by the Sceptics forced the followers of the dogmatic schools (Stoics, Epicureans) to clarify the basis of their theological tenets. Many of the texts that are accessible to us only in a fragmentary state were still highly influential in the early Christian era, so that the reconstruction of the theological views of the Hellenistic philosophers form an important part not only of the history of philosophy, but also of Christian theology and the history of religion in general. One distinctive feature of the volume is that it mirrors the changes of perspective that took place over the many centuries in this area, thus presenting the Hellenistic contribution within the larger framework of Greek philosophical theology.